Prolonged survival after second autologous transplantation and lenalidomide maintenance for salvage treatment of myeloma patients at first relapse after prior autograft. Issue 2 (24th January 2018) - Gössi, Ursina; Jeker, Barbara; Mansouri Taleghani, Behrouz; Bacher, Ulrike; Novak, Urban; Betticher, Daniel; Egger, Thomas; Zander, Thilo; Pabst, Thomas
Abstract: Autologous stem cell transplantation (ASCT) as part of the primary therapy in multiple myeloma (MM) is standard practice. In contrast, the role of a second ASCT (ASCT2) and subsequent lenalidomide maintenance for relapsed disease remains unclear. In this study, we analysed 86 consecutive MM patients with a first relapse after prior ASCT receiving either a second ASCT or conventional chemotherapy. After a median follow‐up of 37.7 months since first relapse, 54 (62.8%) patients were still alive and 29 (33.7%) without progression. Sixty‐one (71.0%) patients received ASCT2 and had better progression‐free survival (PFS) (30.2 versus 13.0 mo; P  = .0262) and overall survival (OS) rates (129.6 versus 33.5 mo; P  = .0003) compared with 25 (29.0%) patients with conventional treatment. Patients relapsing later than 12 months after ASCT1 benefitted from a second ASCT with better PFS2 ( P  = .0179) and OS2 ( P  = .0009). Finally, lenalidomide maintenance after ASCT2 was associated with longer PFS (41.0 vs 21.6 mo; P  = .0034) and better OS (not yet reached vs 129.6 mo; P  = .0434) compared with patients without maintenance. Our data suggest that a second ASCT and lenalidomide maintenance given at first relapse in MM after prior ASCT are associated with better survival rates.